Development of Critical Thinking Skills Based Handout on the Topic of the Human Respiratory System to Improve Science Literacy in Junior High School Students - Antika, Rizky; Fardhani*, Indra; Muttaqiin, Arief; Nugraheni, Dian; Fiel'ardh, Khalifatulloh (Jurnal Pendidikan Sains Indonesia, 2024)
This research focuses on developing handout teaching materials based on critical thinking skills to enhance students' scientific literacy. The study employed the RD development method, along with the ADDIE model. The research subjects included material and media validators, science teachers, and eighth-grade of Junior high school students. The research utilized validation forms, questionnaire responses, pretest, and posttest as instruments. Data analysis techniques involved percentage equation, independent sample t-test, N-gain test, and effect size test. The results indicated that the handouts' quality, as assessed by material validators, was 92.31%, while media validators reported a score of 90.89%, placing both categories in the very decent range. There was a significant difference in average learning outcomes between students who utilize handouts and those who did not. The increase in scientific literacy ability was 0.7, indicating a high category, and the effect size of using handouts is 2.8, denoting a large category. Consequently, handout teaching materials based on critical thinking skills are deemed suitable for improving students' scientific literacy.